A dynamic fracture finite element model of the buried gas transmission pipeline combining soil constraints and gas decompression. (December 2022) - Sun, Dexin; Chen, Yujie; Chao, Haoyu; Jiang, Jiacheng; Li, He; Li, Qun
Highlights: A dynamic fracture finite element model of the buried gas pipeline is established to simulate the actual fracture process incorporating external soil constraints and inner gas decompression. The fracture velocity and crack tip opening angle are calculated using this model, and the effects of internal pipeline pressure and the soil spring stiffness outside the pipe are studied. Abstract: A long-distance natural gas transmission pipeline is the primary solution for natural gas resource distribution. In fact, the longitudinal crack propagation of gas transmission pipelines has always been a concern of the natural gas industry. Because it will cause disastrous accidents once the ductile crack in the pipeline propagates rapidly. Most natural gas transmission pipelines are buried underground to improve the safety of pipeline operation as the backfill soil can absorb energy during the fracture process and restrain the displacements of the flaps. Fracture control is a fundamental requirement for the safe operation of underground pipelines. In this study, the dynamic fracture finite element model of the buried gas pipeline is developed to simulate the actual fracture process instead of the costly full-scale burst experiments. The finite element model incorporates different external soil constraints and internal gas decompression behaviors during pipe rupture in which soil constraints are represented by discrete soil springs, and a user-defined subroutine realizes the gas decompression behavior. The explicit dynamic analysis is employed to simulate the high-speed dynamic fracture process of the pipeline, and the crack propagation is simulated by using the cohesive zone model. Finally, the crack propagation velocity is calculated by this model, and the influence of different internal pressures on the fracture velocity is studied; the crack tip opening angle (CTOA) is predicted, and the effect of soil spring stiffness on CTOA is evaluated.